Energy and Collision Aware WSN Routing Protocol for Sustainable and Intelligent IoT Applications - Patel N.R.; Kumar S.; Singh S.K. (My University, 2025)
Wireless Sensor Network (WSN) has wide range of applications including next generation intelligent IoT applications. Sensor nodes in WSNs don't allow replacing batteries as phenomenon under consideration is not frequently accessible or inaccessible. Resource constrained WSN nodes run on batteries with limited capacity. For long running of the WSNs, energy consumption on each node and lifetime of overall network is a concern for IoT applications. To prolong lifetime of WSNs, use of energy efficient method is necessary and a challenging task. Most of the on-demand routing protocols use metrics like number of hops for the selection of path from the source node to the destination node. Purely hop count-based metrics leads to frequent broken paths as well as more energy consumption and results into reduced lifetime of IoT applications. Method proposed in this paper is a cross layer variant of AODV by replacing hop count metric with link quality and collision count. To establish a path, proposed method fetches link quality information from Physical layer and collision information from MAC layer to aid Network layer for making intelligent routing decisions using ZScore method. Using this information, proposed routing metric caters to select stable and sustainable routing path. Method proposed in this paper is implemented in well-known network simulator, NS-2 by incorporating necessary changes into existing physical and MAC layers as well as AODV protocol. A comparative analysis with existing methods is an indicator of improved performance in terms of energy efficiency, network lifetime, path stability and delay. © 2001-2012 IEEE.